Alternative Journalism as Monitorial Citizenship?: A case study of a local news blog. Issue 5 (3rd July 2016) - Harcup, Tony
Abstract : Recent years have seen claims that some examples of online alternative journalism in the form of hyperlocal and local blogs are helping to address society's "democratic deficit" by subjecting the actions of the powerful to increased public scrutiny, in a process that has been described as "monitorial citizenship". To explore how this might work in practice, this study examines the origins, motivations and practices of one such site in the United Kingdom: the Leeds Citizen . The aim is to provide the sort of detailed consideration in depth that is almost by definition missing from wider surveys of the field. To this end, the case study is based on a series of interviews with the site's creator, augmented by analysis of content, all discussed within the context of scholarly literature on how alternative, non-commercial forms of journalism operate in the digital age. The article concludes that this contemporary form of alternative journalism may indeed be described as an example of monitorial citizenship in action, but there is also a need for further research.